2003
DOI: 10.1194/jlr.m300126-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Transport of cholesterol across a BeWo cell monolayer

Abstract: The placental transport of various compounds, such as glucose and fatty acids, has been well studied. However, the transport of cholesterol, a sterol essential for proper fetal development, remains undefined in the placenta. Therefore, the purpose of these studies was to examine the transport of cholesterol across a placental monolayer and its uptake by various cholesterol acceptors. BeWo cells, which originated from a human choriocarcinoma, were grown on transwells for 3 days to form a confluent monolayer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 93 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…Other investigations demonstrated a greater protein expression level of ABCG1 in BeWo as compared to placenta tissues [48], but again ABCA1 expression was not shown. A study investigating vectorial cholesterol transport in BeWo cells failed to demonstrate the efflux of cholesterol to apoA-1 at the basal (fetal) side [49]. However, basally oriented transport was observed when fetal human serum or phospholipid vesicles were used as acceptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations demonstrated a greater protein expression level of ABCG1 in BeWo as compared to placenta tissues [48], but again ABCA1 expression was not shown. A study investigating vectorial cholesterol transport in BeWo cells failed to demonstrate the efflux of cholesterol to apoA-1 at the basal (fetal) side [49]. However, basally oriented transport was observed when fetal human serum or phospholipid vesicles were used as acceptors.…”
Section: Resultsmentioning
confidence: 99%
“…However, basally oriented transport was observed when fetal human serum or phospholipid vesicles were used as acceptors. Despite the apparent importance of ABCA1-mediated cholesterol efflux, no ABCA1 mRNA or protein expression data were reported [49]. Of note, BeWo cells are derived from a first trimester placenta.…”
Section: Resultsmentioning
confidence: 99%
“…Both these discoveries suggested a possible role of ABCA1 in lipid transport. Schmid et al performed the first studies in humans that demonstrated cholesterol transport from maternal to fetal compartment using BeWo cells as a model of placental monolayer function (21). However, these studies did not precisely determine the involvement of ABCA1 in efflux of cholesterol from placenta.…”
Section: Abc Transporters In the Placentamentioning
confidence: 99%
“…BeWo cells synthesize placental hormones and express trophoblast proteins [reviewed in (18, 19)]. Subclone 30 of BeWo cells becomes a confluent monolayer that is polarized when grown on transwells allowing for the study of unilateral transport across a polarized cell.…”
Section: Transport Of Maternal Cholesterol To the Fetus By The Plamentioning
confidence: 99%
“…In all studies, cells were grown to confluence, and incubated with LDL radiolabeled with cholesteryl ester. After removal of apical LDL, various acceptors were added to the basal side as described (18). The percent cholesterol effluxed is the radiolabel in the basal media as a percentage of radiolabel taken up by the cells.…”
Section: Transport Of Maternal Cholesterol To the Fetus By The Plamentioning
confidence: 99%